Bullying Depicted in Cyberbully Movie - Kamilah, Fitriah Nur; Amelia, Firqo; Wardhani, Dwi Taurina Mila (Institut Agama Islam Negeri Ponorogo, 2022)
This research identified types of bullying and impacts of bullying in Cyberbully movie. The design of this study is qualitative. The method is used to describe and analyze bullying in movie Cyberbully. The data collection was done by watching Cyberbully movie, screen capturing the scenes, and writing down the utterances indicating both the types and impact of bullying. The data analysis was done by classifying the types of bullying in Cyberbully movie by using the theory National Centre against Bullying (2010), finding the impact of bullying in Cyberbully movie by using the theory of Rigby (2003). The finding of the research found that there were twenty data for three types of bullying on the main character in movie Cyberbullying: Verbal bullying, Social bullying ,and Cyberbullying. Here the researchers also managed to find twenty-four data for the impact of bullying which consists of three types, namely: low psychological well-being, poor social adjustment, and psychological distress.